Predictors of retained hemothorax in trauma: Results of an Eastern Association for the Surgery of Trauma multi-institutional trial. Issue 4 (October 2020) - Prakash, Priya S.; Moore, Sarah A.; Rezende-Neto, Joao B.; Trpcic, Sandy; Dunn, Julie A.; Smoot, Brittany; Jenkins, Donald H.; Cardenas, Tatiana; Mukherjee, Kaushik; Farnsworth, Joshua; Wild, Jeffrey; Young, Katelyn; et al.
Abstract : BACKGROUND: The natural history of traumatic hemothorax (HTX) remains unclear. We aimed to describe outcomes of HTX following tube thoracostomy drainage and to delineate factors that predict progression to a retained hemothorax (RH). We hypothesized that initial large-volume HTX predicts the development of an RH. METHODS: We conducted a prospective, observational, multi-institutional study of adult trauma patients diagnosed with an HTX identified on computed tomography (CT) scan with volumes calculated at time of diagnosis. All patients were managed with tube thoracostomy drainage within 24 hours of presentation. Retained hemothorax was defined as blood-density fluid identified on follow-up CT scan or need for additional intervention after initial tube thoracostomy placement for HTX. RESULTS: A total of 369 patients who presented with an HTX initially managed with tube thoracostomy drainage were enrolled from 17 trauma centers. Retained hemothorax was identified in 106 patients (28.7%). Patients with RH had a larger median (interquartile range) HTX volume on initial CT compared with no RH (191 [48–431] mL vs. 88 [35–245] mL, p = 0.013) and were more likely to be older with a higher burden of thoracic injury. After controlling for significant differences between groups, RH was independently associated with a larger HTX on presentation, with a 15% increase in risk of RH for each additional 100 mL of HTX on initial CT imaging (odds ratio, 1.15; 95% confidence interval, 1.08–1.21; p < 0.001). Patients with an RH also had higher rates of pneumonia and longer hospital length of stay than those with successful initial management. Retained hemothorax was also associated with worse functional outcomes at discharge and first outpatient follow-up. CONCLUSION: Larger initial HTX volumes are independently associated with RH, and unsuccessful initial management with tube thoracostomy is associated with worse patient outcomes. Future studies should use this experience to assess a range of options for reducing the risk of unsuccessful initial management. LEVEL OF EVIDENCE: Therapeutic/care management study, level III. Abstract : Supplemental digital content is available in the text.